Measuring the Impact of Nuclear Interaction in Particle Therapy and in Radio Protection in Space: the FOOT Experiment - Battistoni, Giuseppe; Toppi, Marco; Patera, Vincenzo; The FOOT Collaboration, (Frontiers in Physics, 2021)
In Charged Particle Therapy (PT) proton or 12C beams are used to treat deep-seated solid tumors exploiting the advantageous characteristics of charged particles energy deposition in matter. For such projectiles, the maximum of the dose is released at the end of the beam range, in the Bragg peak region, where the tumour is located. However, the nuclear interactions of the beam nuclei with the patient tissues can induce the fragmentation of projectiles and/or target nuclei and needs to be carefully taken into account when planning the treatment. In proton treatments, the target fragmentation produces low energy, short range fragments along all the beam path, that deposit a non-negligible dose especially in the first crossed tissues. On the other hand, in treatments performed using 12C, or other (4He or 16O) ions of interest, the main concern is related to the production of long range fragments that can release their dose in the healthy tissues beyond the Bragg peak. Understanding nuclear fragmentation processes is of interest also for radiation protection in human space flight applications, in view of deep space missions. In particular 4He and high-energy charged particles, mainly 12C, 16O, 28Si and 56Fe, provide the main source of absorbed dose in astronauts outside the atmosphere. The nuclear fragmentation properties of the materials used to build the spacecrafts need to be known with high accuracy in order to optimise the shielding against the space radiation. The study of the impact of these processes, which is of interest both for PT and space radioprotection applications, suffers at present from the limited experimental precision achieved on the relevant nuclear cross sections that compromise the reliability of the available computational models. The FOOT (FragmentatiOn Of Target) collaboration, composed of researchers from France, Germany, Italy and Japan, designed an experiment to study these nuclear processes and measure the corresponding fragmentation cross sections. In this work we discuss the physics motivations of FOOT, describing in detail the present detector design and the expected performances, coming from the optimization studies based on accurate FLUKA MC simulations and preliminary beam test results. The measurements planned will be also presented.